Automatic slope streak detection on Mars - Puga, Fernanda [UNESP] (2015)
An algorithm to detect slope streaks on Mars is presented in this paper. It is mainly based on morphological operators and consists of three steps: 'pre-processing' with connected operators to filter small structures and shadows, 'detection' with top-hat, Otsu binarisation and thinning/pruningre-construction operations and by a 'post-processing' to remove non-elongated objects. The algorithm is successfully tested on very high resolution images (0.25-6.5 m/pixel) of HiRISE and MOC cameras on different locations of Mars.